Isolated Joint Block Progression Training Improves Leaping Performance in Dancers - Rice, Paige E.; Nishikawa, Kiisa; Nimphius, Sophia (Frontiers in Sports and Active Living, 2021)
The purpose of this study was to investigate the effect of a 12-week ankle-specific block progression training program on saut de chat leaping performance (leap height, peak power (PP), joint kinetics and kinematics), maximal voluntary isometric plantarflexion (MVIP) strength, and Achilles tendon (AT) stiffness. Dancers (training group n = 7, control group n = 7) performed MVIP at plantarflexed (10˚) and neutral ankle positions (0˚) followed by ramping isometric contractions equipped with ultrasound to assess strength and AT stiffness, respectively. Dancers also performed saut de chat leaps surrounded by 3-D motion capture atop force platforms to determine center of mass and joint kinematics and kinetics. The training group then followed a 12-week ankle-focused program including isometric, dynamic constant external resistance, accentuated eccentric loading, and plyometric training modalities, while the control group continued dancing normally. We found that the training group’s saut de chat ankle PP (59.8%), braking ankle stiffness (69.6%), center of mass PP (11.4%), and leap height (12.1%) significantly increased following training. We further found that the training group’s MVIP significantly increased at 10˚ (17.0%) and 0˚ (12.2%) along with AT stiffness (29.6%), while aesthetic leaping measures were unchanged (peak split angle, mean trunk angle, trunk angle range). Ankle-specific block progression training appears to benefit saut de chat leaping performance, PP output, ankle-joint kinetics, maximal strength, and AT stiffness, while not affecting kinematic aesthetic measures. We speculate that the combined training blocks elicited physiological changes and enhanced neuromuscular synchronization for increased saut de chat leaping performance in this cohort of dancers.